Selecting and Scaling of Energy-Compatible Ground Motion Records - Papazafeiropoulos, George; Georgioudakis, Manolis; Papadrakakis, Manolis (Frontiers in Built Environment, 2019)
We propose a novel spectra-matching framework, which employs a linear combination of raw ground motion records to generate artificial acceleration time histories perfectly matching a target spectrum, taking into account not only the acceleration but also the seismic input energy equivalent velocity. This consideration is leading to optimum acceleration time histories which represent actual ground motions in a much more realistic way. The procedure of selection and scaling of the suite of ground motion records to fit a given target spectrum is formulated by means of an optimization problem. Characteristic ground motion records of different inherent nature are selected as target spectra, to verify the effectiveness of the algorithm. In order to assess the robustness and accuracy of the proposed methodology the seismic performance of single- and multi- degree of freedom structural systems has been also considered. The portion of the seismic input energy that is dissipated due to viscous damping action in the structure is quantified. It is shown that there exists a good agreement between the target and optimized spectra for the different matching scenarios examined, regardless of the nature of target spectra, demonstrating the reliability of the proposed methodology.